Pengembangan Aplikasi E-Commerce Menggunakan Metode Web Information System Development Methodology (Studi Kasus: Jaks Store.Id) - Mochamad Iqsal Alfiansyah; Mochamad Bagoes Satria Junianto (Program Studi Sistem Informasi, Universitas Multi Data Palembang, 2023)
The jaks_store.id shop is a shop that sells various kinds of adventure tools such as camping tents, flysheets, sleeping bags, etc. this store was founded in 2020 at the beginning of covid-19 this jaks_store.id store already uses internet media, namely Instagram and Whatsapp with a total of 40 products, even though it has used Instagram and Whatsapp media, marketing is still not optimal and also the jaks_store.id store in processing data product and sales data still use manual input methods so that errors often occur in terms of inputting data both from inputting product data and from product sales results. Therefore, jaks_store.id requires an E-Commerce website-based sales facility or service to make it easier for stores to process product data and also add up product sales results so that there are no errors in inputting products back and also with this E-commerce customers can also facilitated in terms of transacting online. In its development using the WSDM method and also using the PHP programming language and using MySQL and UML (Unified Modeling Language) including use case diagrams, activity diagrams and class diagrams. With the development of this system, it is hoped that it can help this jaks_store.id store in managing products so that there are no errors in inputting goods.